Usage analysis of the Nursing Activities Score in two Spanish ICUS - Carmona-Monge, Francisco Javier; Uranga, Ikerne Uria; Gomez, Sonia Garcia; Herranz, Cristina Quiros; Bengoetxea, Maitane Bergaretxe; Unanue, Goiatz Etxabe; Martin, Alazne Iribarren; Hernando, Maialen Echepetelecu; Saralegui, Erika Badiola; Irazoqui, Miren Auzmendi (Revista da Escola de Enfermagem da USP, 2013)
The aim of this study was to analyze the discourse of health managers on aspects related to delay in tuberculosis diagnosis. This was a qualitative research study, conducted with 16 Family Health Unit managers. The empirical data were obtained through semi-structured interviews. The analysis was based on the theoretical framework of the French school of discourse analysis. According to the managers’ statements, the delay in tuberculosis diagnosis is related to patient and health service aspects. As for patient aspects, managers report fear, prejudice and lack of information as factors that may promote a delayed diagnosis. Regarding health service aspects, structural problems and lack of professional skills were reported. The discourse of managers should be considered to qualify tuberculosis control actions and to prevent delays in diagnosis.